2021
DOI: 10.1186/s13756-021-00892-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of targeted educational intervention towards public knowledge and perception of antibiotic use and resistance in the state of Perak, Malaysia

Abstract: Background Antibiotic resistance is a major public health concern, accelerated by antibiotic overuse. Inadequate knowledge among the public has been associated with inappropriate use of antibiotics. This study determined the impact of a self-developed educational leaflet for addressing specific knowledge gaps in antibiotic use among the public. Methods This was an experimental study conducted at five hospitals and 20 primary health care clinics in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…The regression analysis results of the present study show that the belief in antibiotic effectiveness is the strongest predictor of antibiotic use, followed by negative attitudes, positive attitudes, and health anxiety. The importance of beliefs, attitudes, and knowledge has been demonstrated earlier in several studies conducted, for example, in Australia [19], Ethiopia [21], Malaysia [23], Poland [22], and in various European countries [8]. In addition, these studies indicate that beliefs, attitudes, and knowledge are interrelated: correct beliefs require a certain level of knowledge, and attitudes are formed according to the beliefs.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…The regression analysis results of the present study show that the belief in antibiotic effectiveness is the strongest predictor of antibiotic use, followed by negative attitudes, positive attitudes, and health anxiety. The importance of beliefs, attitudes, and knowledge has been demonstrated earlier in several studies conducted, for example, in Australia [19], Ethiopia [21], Malaysia [23], Poland [22], and in various European countries [8]. In addition, these studies indicate that beliefs, attitudes, and knowledge are interrelated: correct beliefs require a certain level of knowledge, and attitudes are formed according to the beliefs.…”
Section: Discussionmentioning
confidence: 65%
“…Educational interventions and campaigns targeting especially the misuse of antibiotics for viral illnesses should be prioritised [23,24]. In an experimental study conducted in Malaysia, a short (15 min) educational session by the pharmacists improved participants' knowledge and perception towards antibiotic use and knowledge towards antibiotic resistance [23]. Similarly, Thorpe et al demonstrated in their experimental study conducted in the UK that providing antibiotic information substantially diminishes inappropriate expectations of antibiotics [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another scientific knowledge that has a direct impact on learners is antimicrobial resistance. Most research findings supported the idea that information campaigns on antibiotics consumption changed attitudes and behaviors (Azevedo et al, 2013;Lee et al, 2015;Thong et al, 2021). Recognizing the threat of antimicrobial resistance to global health and food security, the DepEd has been championing antimicrobial stewardship through its policies, such as during World Antibiotic Awareness Week (WAAW).…”
Section: Discussionmentioning
confidence: 82%